On-Surface Hydrogenation of Buckybowls: From Curved Aromatic Molecules to Planar Non-Kekulé Aromatic Hydrocarbons - Wäckerlin, Christian; Gallardo, Aurelio; Mairena, Anaïs; Baljozović, Miloš; Cahlík, Aleš; Antalík, Andrej; Brabec, Jiří; Veis, Libor; Nachtigallová, Dana; Jelínek, Pavel; Ernst, Karl-Heinz (ACS nano, 2020)
Functionalization of surfaces with derivatives of Buckminsterfullerene fragment molecules seems to be a promising approach toward bottom-up fabrication of carbon nanotube modified electrode surfaces. The modification of a Cu(100) surface with molecules of the buckybowl pentaindenocorannulene has been studied by means of scanning tunneling microscopy, carbon monoxide-modified noncontact atomic force microscopy, time-of-flight secondary mass spectrometry, and quantum chemical calculations. Two different adsorbate modes are identified, in which the majority is oriented such that the bowl cavity points away from the surface and the convex side is partially immersed into a four-atom vacancy in the Cu(100) surface. A minority is oriented such that the convex side points away from the surface with the five benzo tabs oriented basically parallel to the surface. Thermal annealing leads to hydrogenation and planarization of the molecules in two steps under specific C-C bond cleavage. The benzo tabs of the convex side up species serve as a hydrogen source. The final product has an open-shell electron structure that is quenched on the surface.
Keywords: scanning probe microscopy; open-shell aromatic hydrocarbons; on-surface chemistry; buckybowls; density functional theory